Nanocomposite Materials alfa-Fe2O3 / gamma-Fe2O3:Synthesis, Crystal and Magnetic Microstructure, Morphology - V.О. Kotsyubynsky; V.V. Mokliak; A.B.Grubiak; P.I. Kolkovsky; Al-Saedi Abdul Halek Zamil (Журнал нано- та електронної фізики)
The paper studies the relationship between the synthesis conditions of nanocomposites α-Fe2O3 /  γ-Fe2O3 and the phase composition, morphology, crystal and magnetic microstructures of these materials.